Periphery Dichotomy and its Investigation by GIS Methods - Pénzes, János (Acta Geographica Debrecina Landscape & Environment series, 2016)
Centre-periphery dichotomy can be regarded as one of the crucial issues in human geography and regional science. The definition of periphery is far from unambiguous due to its relative expression and its content. This is the reason why can significant number of studies be found focusing on the delimitation of central and peripheral areas. The revolution of computer technology and the rapid development of GIS cause the more and more extended usage of these techniques in the human geography as well. These related studies were categorised by their approaches – namely the locational or developmental centreperiphery concepts – and their GIS tools. Application of spatial parameters with extended datasets and complex GIS based calculations mean the most precise and complicated use of GIS and computer tools in the delimitation of peripheral (and central) areas.